Back Cover: In Situ Assembly of Choline Acetyltransferase Ligands by a Hydrothiolation Reaction Reveals Key Determinants for Inhibitor Design (Angew. Chem. Int. Ed. 2/2021). Issue 2 (28th December 2020) - Wiktelius, Daniel; Allgardsson, Anders; Bergström, Tomas; Hoster, Norman; Akfur, Christine; Forsgren, Nina; Lejon, Christian; Hedenström, Mattias; Linusson, Anna; Ekström, Fredrik
Abstract : In situ hydrothiolation solves a 50‐year SAR conundrum: In their Research article on page 813, Fredrik Ekström and co‐workers describe an in situ inhibitor assembly catalyzed by choline acetyltransferase. Using a series of prototypical arylvinylpyridinium‐based compounds previously believed to be inhibitors, they show that these compounds are actually substrates in a coenzyme A‐dependent hydrothiolation reaction that yields the active inhibitors. The reaction product within the enzyme catalytic site is illustrated.